Exploration of phytoconstituents of Medhya Rasayana herbs to identify potential inhibitors for cerebroside sulfotransferase through high-throughput screening - Singh, Nivedita; Singh, Anil Kumar (Frontiers in Molecular Biosciences, 2024)
Cerebroside sulfotransferase (CST) is key enzyme in sulfatide biosynthesis and regulation of myelin sheath in the nervous system. To counter sulfatide accumulation with deficiency of Aryl sulfatase A, CST is considered a target protein in substrate reduction therapy in metachromatic leukodystrophy. In this study, 461 phytoconstituents from four herbs of Medhya Rasayana were screened using multi-pronged virtual screening methods including molecular docking, MD simulation, and reverse pharmacophore analysis. The initial screening of the top 15 hits was based on the binding affinity of the compounds toward the CST substrate binding site using the lowest free energy of binding score cutoff of ≤-7.5 kcal/mol with number of conformations in largest cluster more than 75. The ADME and toxicity based pharmacokinetic analysis delivered top four hits: 18alpha-Glycyrrhetinic acid, Lupeol, Alpha carotene, and beta-Carotene, with high blood brain barrier permeability and negligible toxicity. 100 ns simulation of proteinligand complexes with trajectory analysis of structural deviation, compactness, intramolecular interactions, principal component analysis, free energy landscape, and dynamic cross correlation analysis showed the binding potential and positioning of four hits in the binding pocket. Thus, in depth analysis of protein-ligand interaction from pre-and post-molecular dynamic simulation along with reverse pharmacophore mapping suggest that 18alpha-Glycyrrhetinic acid is the most potent and specific CST inhibitor, while beta-Carotene could be considered the second most potent compound for CST inhibition as it also exhibited the overall stability throughout the simulation. Therefore, the computational drug screening approach applied in this study may contribute to the development of oral drugs as therapeutic option for metachromatic leukodystrophy.